The impact of mobile phones on survey measurement error - Peter Lynn; Olena Kaminska (University of Essex, Institute for Social and Economic Research (ISER), 2011)
Mobile phone survey interviewing is becoming increasingly prevalent, so it is important to understand how it affects measurement error. We link cognitive response process theory (Tourangeau et al 2000) to theories of mode effects to build a comprehensive framework that identifies ways in which the different context of mobile interviews and differences inherent in the technology can influence survey responses. We evaluate elements of the framework using data from a randomised experiment in which respondents were assigned to be interviewed either by mobile or fixed phone and in which relevant measures of interview context were gathered. Our findings address causes of survey error resulting from mode of data collection, both in general and in the specific context of mobile phones. We also outline needed future research.
Keywords: C81; C83; 330; interview context; satisficing; social desirability bias; Meinungsforschung; Befragung; Mobiltelefon; Statistischer Fehler